In the catskills and my boyhood - Burroughs, John, 1837-1921 (New York classics, 2021)
Henry James called John Burroughs (1837-1921) 'a more humorous, more available, and more sociable Thoreau.' Walt Whitman in turn extolled Burroughs as 'a child of the woods, fields, hills--native to them in a rare sense (in a sense almost a miracle).' Throughout his many books and essays, Burroughs was never more eloquent on nature themes than when writing about his native countryside: the woods, streams, and mountains of the Catskills in New York. In the Catskills collects the very best of Burroughs's writings about his birthplace in a book that is sure to be treasured by all lovers of the region as well as lovers of the literature of nature. This new edition includes an introduction by Burroughs biographer Edward Renehan and an additional work not included in previous editions, entitled My Boyhood.